The Influence of Corporate Governance, Leverage, and Institutional Ownership on Tax Avoidance With Board Gender Diversity as Moderating Variable - Khadidjah Dinda Maharani; Tiara Pandansari; Ani Kusbandiyah; ​Siti Nur Azizah (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2025)
This study investigates the influence of corporate governance, leverage, and institutional ownership on tax avoidance, with board gender diversity serving as a moderating variable, in property and real estate companies listed on the Indonesia Stock Exchange from 2015 to 2024. Based on 144 observations from 18 purposively selected firms, tax avoidance was measured using the Effective Tax Rate (ETR), corporate governance, leverage, institutional ownership and gender diversity by the percentage of female directors. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) in SPSS 26. The findings indicate that corporate governance and leverage does not have a significant effect on tax avoidance, while institutional ownership and board gender diversity has significantly on tax avoidance. Board gender diversity moderates the relationship between institutional ownership and corporate governance on tax avoidance but does not moderate the effects of leverage.